(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Development is unavoidable. Communication occurs unconsciously. Communication for Development may change society strategically. Development Communication can intentionally improve people’s lives. Developing nations communicate the issues of poverty, health, gender, and social justice in media. Development Communication connects stakeholders, fosters positive change, benefits individuals, and advances society. Cross-sector communication is needed for improved feeding practices, nutritional issues, healthier lifestyles, cleanliness, hygiene, etc. It might be for education, climate change, trash management, plastics, etc. This paper examines Kerala students’ sustainable development communication strategies. The study analyses two prominent Kerala newspaper articles on sustainable development communication tactics. The reports span covers June 1, 2022, to May 31, 2023. Content analysis showed four instructional communication styles. The four approaches are curricular, cocurricular, innovation, and communicative barriers to sustainable development education. This study can inform the school’s sustainable development-focused curriculum.